Stress, Anxiety, and Depression among Teachers during the COVID-19 Pandemic - Asiyeh Pirzadeh; Zahra Abotalebi; Roya Riahi (Shiraz University of Medical Sciences, 2023)
Background: Mental disorders have become especially important in the current stressful world. Among these disorders, anxiety, and depression are highly prevalent. Stress is also a very common phenomenon. Given the teachers' prominent roles in the education department and the importance of their mental health, the present study aimed to determine stress, anxiety, and depression among teachers during the COVID-19 Pandemic in 2020.Methods: This cross-sectional study examined 210 primary school teachers in district 3 of Isfahan province in Iran, using multi-stage random sampling. Data were collected by the Depression, Anxiety, and Stress Scale- 42 Items (DASS-42). Also, the obtained data were analyzed using SPSS Statistics 20 and conducting pearson test, t-test, ANOVA, and linear regression.Results: The results indicated a high level of stress, anxiety, and depression among the teachers. Findings also showed that teachers' depression was significantly associated with their age, work experience, type of housing, and student behavior (P<0.05). Further, teachers' anxiety was significantly associated with their work experience and student behavior (P<0.05). Moreover, teachers' stress was significantly associated with their history of mental diseases (P<0.05). Teachers' depression, anxiety, and stress were not significantly correlated with their marital status, spouse's job, education level, and Relationship with other colleagues (P>0.05).Conclusion: Given that stress, anxiety, and depression affect teachers' mental health, and consequently the quantity and quality of their work, holding training courses and sessions to discuss teachers' problems, provides practical and effective solutions, and offers them administrative and organizational support, can be an effective step towards improving their mental health.